(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article scientifically addresses the use of economic analysis methods in conducting private equity audits. Conclusions were made using case studies in the coverage of the topic. Also, based on foreign experience, the proposal to publish the main financial ratios in tabular form in accordance with the requirements of IFRS when publishing financial statements of enterprises in the open press.